Assessing Radiosensitivity: Effects of Acute Ionizing Radiation on Inflammation and Apoptosis in Macrophage Cell Line (RAW 264.7): Effect of radiation on inflammation and apoptosis - Bagheri-Hosseinabadi, Zahra; Zafari, Jaber; Javani Jouni, Fatemeh; Sadeghi, Hanieh; Abbasifard, Mitra (Journal of Lasers in Medical Sciences, 2023)
Introduction: The responses of biological systems to various types of radiation have multifaceted dimensions. In the field of ionizing radiation, in vitro external gamma radiation therapy has primarily been studied as a model to elucidate the challenges that biological systems face from radiation effects. Exposure of cells/organisms to gamma radiation results in a cascade of ionization events that can cause severe and irreversible biological damage. However, the biological responses and oxidative stress-related mechanisms under acute radiation conditions remain poorly understood in inflammatory systems. The present study aimed to provide a model of the effect of ionizing radiation on macrophages, which play a pivotal role in the mechanisms of inflammation, to assess the impact of radiotherapy as an approach to treating inflammatory diseases. Methods: A macrophage cell line (RAW 264.7) was cultured and exposed to different doses of gamma radiation (4, 6, 8, 10 Gy). Cell viability, apoptosis, cell cycle, migration, nitric oxide (NO) and prostaglandin E2 (PGE2) production, expression of pro-inflammatory and apoptotic genes, and cytokine secretion of macrophages were also evaluated. Results: The results showed that gamma radiation at 4 Gy had a low effect on macrophage characteristics and cytokine secretion patterns. In contrast, higher doses (8 and 10 Gy) increased DNA damage, expression of apoptotic genes, and secretion of NO and PGE2 cytokines. 6 Gy radiation, the maximum radiation dose, showed moderate non-destructive effects and inflammation process modulation. In this study, doses higher than 6 Gy of Gamma radiation caused cell mortality. Conclusion: It appears that 6 Gy of gamma radiation modulates the inflammatory cascade caused by macrophage cells.